Spiritualitas sebagai Kekuatan di Masa Tua: Pendekatan Pastoral yang Membantu Lansia Menemukan Makna Hidup - Agustina Hutagalung; Rencan Carisma Marbun (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2025)
The significant increase in the elderly population in Indonesia, along with the rise in global life expectancy, presents new challenges for their well-being, both physically, emotionally, and socially. One of the main challenges faced is the sense of lost meaning in life, which is exacerbated by physical limitations, the loss of a spouse, and social isolation. This study aims to explore the role of spirituality in empowering the elderly to find meaning in life through a pastoral approach. Using a qualitative case study approach, this research identifies the challenges faced by the elderly and analyzes how spirituality and pastoral approaches can enhance their lives. Data were gathered through in-depth interviews, participatory observation, and document analysis, and were subsequently analyzed using thematic methods. The results show that spirituality provides the elderly with strength to face life’s challenges, such as prayer, worship, and involvement in faith communities. Effective pastoral approaches include emotional counseling, Bible teaching, and engaging the elderly in spiritual community activities. This approach helps the elderly discover new hope and purpose in life, allowing them to live their later years more meaningfully. This study contributes to the development of pastoral care for the elderly and strengthens the role of spirituality in supporting their well-being.